The sports world in the era of COVID-19 - Nauright, J.; Zipp, S.; Kim, Y. H. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
The entire world was turned on its head with the widening impact of COVID-19 during the first half of 2020. With competitions cancelled or postponed, millions of dollars were lost in predicted revenue. Clubs and franchises in major leagues were able to survive due to lucrative television contracts, and, once play resumed, help mitigate some of the losses of revenue from spectators attending matches. When soccer resumed in four of the five main leagues in Europe by July 2020, matches were played in empty stadia, though fan chanting was piped over the airways to resemble a match-day atmosphere for spectators. Key events like the Open Golf Championship in the United Kingdom were cancelled while other such as the US Masters golf tournament were moved from Spring to Autumn. Clubs and organizations lost billions as a result of pandemic cancellations. As Swanson and Smith explain in this issue, the decision to cancel the March Madness college basketball tournament in the USA cost universities $375 million in lost revenues.